1999
DOI: 10.1037/0735-7028.30.5.504
|View full text |Cite
|
Sign up to set email alerts
|

Therapist-client sex: Clients' retrospective reports.

Abstract: Therapists will be more effective practitioners when they understand the factors that contribute to sexual boundary violations. The authors' interviews with former victims indicated that offending therapists were mostly reputable psychologists working alone, and that boundary violations developed gradually. The clients were often victims of child sexual abuse. Many reported pleasurable feelings during the affair but saw the experience as hurtful or exploitative in retrospect. The authors' findings imply that p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
19
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 25 publications
(16 reference statements)
4
19
0
1
Order By: Relevance
“…These results add to previous findings (Somer & Saadon, 1999) suggesting that clients may experience pleasurable feelings during sexual contacts with their psychotherapists. There are at least two possible interpretations for the seemingly high rate of TCS-Romance to TCS-Abuse accounts.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…These results add to previous findings (Somer & Saadon, 1999) suggesting that clients may experience pleasurable feelings during sexual contacts with their psychotherapists. There are at least two possible interpretations for the seemingly high rate of TCS-Romance to TCS-Abuse accounts.…”
Section: Discussionsupporting
confidence: 86%
“…This practitioner argued that the only suffering that can result from therapist-patient sex, and the only reason why a patient might "complain against the previous mutual agreement to engage in sexual interaction that she negotiated with her therapist" (p. 81), were that the results did not meet "her self-imposed expectations" and her anger at the failure of the therapist to "satisfy her dreams of either marrying her or compensating her financially" (p. 82). Only few data exist to suggest that TCS clients may experience some positive feelings during the aberrant affair (e.g., Somer & Saadon, 1999). The literature on patient perceptions of TCS is very sparse and nothing is known on the exploited clients' constructions of the meaning of the relationship during TCS.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…Investigations on the clients' perspectives are sparse (e.g. Ditch & Avery, 2001;Somer & Saadon, 1999), and qualitative studies on developing emotional processes among survivors of TCS may not have been done. In fact, no such research has been identified by the authors of this study.…”
Section: Introductionmentioning
confidence: 97%
“…A number of quantitative studies have examined the role of peri-traumatic dissociation in the development of PTSD (e.g., Shalev, Freedman, Peri, Brandes, & Sahar, 1997;Shalev, Peri, & Canetti, 1996) and identified it as significantly predictive of PTSD symptomatology four months following exposure to the traumatic event (Freedman, Brandes, Peri, & Shalev, 1999). Several Israeli qualitative studies have shown that peri-traumatic dissociation plays an important role in the sexual victimization of female clients by their male psychotherapists (e.g., Ben Ari & Somer, 2004;Somer & Nachmani, in press;Somer & Saadon, 1999) and in the coping of emergency room social workers vicariously traumatized during terror attacks (Peled-Avram, Ben-Yizhack, Gagin, Somer, & Buchbinder, 2004;.…”
Section: Introductionmentioning
confidence: 99%